From reading to writing genomes: a new direction in ELSI - Mikami, Koichi (Frontiers in Genetics, 2025)
In this commentary piece, I discuss what the growing interest in synthesizing DNA at large scale means to the effort to address the Ethical, Legal and Social implications (ELSI) of genetic/genomic research. The idea that the latest scientific research should be accompanied by efforts to explore and then address its ELSI first materialized in the context of the Human Genome Project (HGP). This project to read a human genome was completed in 2003, but the science of genomics has advanced since. Particularly important was successful synthesis of phiX174 bacteriophage genome in the very year that the HGP was concluded. This work opened up a new direction in genomics research centering on genome-scale synthesis and re-designing of genomes, characterized as a ‘writing’ approach. While early targets in this line of research were microorganisms like Escherichia coli and Saccharomyces cerevisiae, technological advancements in the synthesis of large-scale DNA sequences as well as methods to assemble them into a single genome or a chromosome are being made, and in 2016 a team of scientists proposed to ‘write’ an entire human genome. This line of scientific research, I argue, has two major characteristics, its scale and emphasis on design, and demands discussions around ‘ELSI of re-designing,’ in contrast to ELSI discussions that predominated in the earlier ‘reading’ paradigm of genomics. Because of these differences, efforts to address this ELSI of re-design should entail re-thinking what we do as ELSI as well as how we do it.